Individual Roles of Network and Sheet Solids in Architectured Porous Materials - Yang, Nan; Fan, Siping; Zhuang, Juncheng; Zhang, Yubo; Qian, Zheng (Frontiers in Physics, 2022)
To understand the different roles played by sheet solids and network solids in complex porous biomaterials/native tissues, we designed a new kind of nature-inspired structure comprising these two solids by using triply periodic minimal surfaces (TPMS) and Voronoi diagrams using CAD method, and compared them with the previously reported Poisson-Voronoi (PV) solids that only comprise network solids. Here we show that the sheet solids contribute greater stiffness and solid/void interface than the network solids, and our TPMS-Voronoi (TV) solids can improve/tune both the elastic moduli and specific surfaces even at fixed solid volume fraction (SVF), and can be stiffer than the PV solids. This can directly guide the porous materials design for use in tissue engineering and aerospace.